An Analysis of Facebook Activities on The Positive and Negative Effect Toward Elementary School Students (Journal of Primary Education, 2018)
The purpose of this study was to analyze the influence of the social network of facebook on the positive and negative effect toward Elementary School students in Demak. This study applied descriptive qualitative approach with case study research design. The source of data in this study obtained from the purposive sampling technique at elemeentary school in Sector Three of Kebonagong, Demak whose parents work as teachers, farmers, entrepreneurs, military and police officers. Data collection methods applied in this study were observation, semi-structured interviews and documentation study. The data analysis was done by using an interactive model analysis. The trustworthiness of data was confirmEd by using triangulation and resources technique. The result of the analysis showed that the social media of facebook is used by the students to do interaction with other students to share each other informations related to learning task, to remind each other, and to improve the English language skills. The control system of the activities of students maybe significantly influenced by their parents’ profession. At various jobs of parents which require them to stay in the workplace, will lead to less control of parents or give more freedom to their children in using social accounts. In this case, it happened to parents whose profession were entrepreneur. The control system of for profession of teachers, farmers, police officer, and military officer provide more time to their children of give more supervision on their children’ accounts so that their control system is better than those who work as enterpreneur.